A rare case of inflammatory myofibroblastic tumour in the maxillary sinus: masquerading a malignancy - Kumar, E. Siva; Swapna, C. A.; Karanam, Lavanya; Radhika, S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Aim establishing the diagnosis of inflammatory myofibroblastic tumour is very challenging due to its varied clinical and radiological manifestations. We report a rare presentation of a 5 years old female child with inflammatory myofibroblastic tumour, which was endoscopically resected with postop steroid therapy. Case report, a 5 years old female child presented to ENT OPD with complaints of right nasal obstruction since, 4 months along with recurrent minor episodes of spontaneous bleeds from the right nasal cavity. On examination a huge fleshy reddish polypoidal and pulsatile mass was seen filling the entire right nasal cavity associated with right eye proptosis. MRI with contrast showed expansion of right maxillary sinus bony walls with internal soft tissue leision measuring 41 mm (TRANS) × 36 mm (AP)×31 mm (CC) seen enhancing with contrast. Vascular supply is from maxillary artery. Under anaesthesia right external carotid artery ligation was done followed by removal of mass from right nasal cavity. Histopathological examination was consistent with inflammatory myofibroblastic tumour. On immunohistochemistry spindle cells showed cytoplasmic positivity for SMA. Inflammatory myofibroblastic tumour though a very unusual tumour, should be considered in the differential diagnoses of tumours in the nasal cavity. A vigilant clinical evaluation and extensive imaging along with histopathological examination can guide us to an early diagnosis and proper treatment resulting in better patient satisfaction.